2020
DOI: 10.1002/jpen.1817
|View full text |Cite
|
Sign up to set email alerts
|

Determining Optimal Outcome Measures in a Trial Investigating No Routine Gastric Residual Volume Measurement in Critically Ill Children

Abstract: Background Choosing trial outcome measures is important. When outcomes are not clinically relevant or important to parents/patients, trial evidence is less likely to be implemented into practice. This study aimed to determine optimal outcome measures for a trial of no routine gastric residual volume (GRV) measurement in critically ill children. Methods A mixed‐methods approach was used: a focused literature review, parent and clinician interviews, a modified 2‐round Delphi, and a stakeholder consensus meeting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…If a GRV is >50% of the last bolus feed, it is returned, and if this recurs 2 hours later, the individual's GET is redefined. The literature suggests abandoning GRVs to direct feeding and highlights a need for alternative bedside tools to measure gastric emptying 23,38–41 . We acknowledge that GRVs are inaccurate, as shown by a laboratory simulation 42 ; do not take account of gastric juices or swallowed secretions; do not predict delayed gastric emptying with continuous feeding 43 ; do not affect development of ventilator‐associated pneumonia 44,45 ; and are not recommended by ASPEN 1 to drive EN advancement.…”
Section: Discussionmentioning
confidence: 99%
“…If a GRV is >50% of the last bolus feed, it is returned, and if this recurs 2 hours later, the individual's GET is redefined. The literature suggests abandoning GRVs to direct feeding and highlights a need for alternative bedside tools to measure gastric emptying 23,38–41 . We acknowledge that GRVs are inaccurate, as shown by a laboratory simulation 42 ; do not take account of gastric juices or swallowed secretions; do not predict delayed gastric emptying with continuous feeding 43 ; do not affect development of ventilator‐associated pneumonia 44,45 ; and are not recommended by ASPEN 1 to drive EN advancement.…”
Section: Discussionmentioning
confidence: 99%
“…A survey in UK PICUs showed that routine measurement of GRV was part of the standard practice, which shows that translation of evidence into practice take time and effort and we wanted to achieve low hanging fruit first (29). There have been some recent works to determine the patients related outcomes of trials studying effects of measuring or not measuring GRV (30,31).…”
Section: Limitationmentioning
confidence: 99%
“…In line with the Medical Research Council's framework for complex intervention development [23] conducting trial feasibility studies can help mitigate these challenges and establish whether the trial is acceptable to parents and practitioners, and practical to conduct [24,25]. As part of a pre-trial feasibility study [14,26], we explored parent and practitioner perspectives on the acceptability of conducting a clinical trial comparing no routine GRV measurement (the intervention) to routine GRV measurement in UK neonatal intensive care units (NNU) and paediatric intensive care unit (PICU) settings.…”
Section: Introductionmentioning
confidence: 99%